Collaborative Strategies for Managing Mangrove Ecotourism: Raising Awareness and Stakeholder Participation in Sustainable Tourism - Dian Irmayanti (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2024)
The purpose of this research is to identify and develop collaborative strategies in managing mangrove ecotourism with a focus on increasing awareness and stakeholder participation in sustainable tourism. This research aims to explore ways to increase community awareness and stakeholder involvement in sustainable mangrove ecotourism management efforts.This research uses a qualitative approach with an explanatory case study method, because this research investigates and describes the complexity in the context of stakeholder involvement in the development of edu-ecotourism in Lembur Mangrove Patikang, Pandeglang. Data collection techniques used in-depth interviews, document study and observation. Data collection techniques used in-depth interviews, document study and observation. The Edu-Ecotourism Mangrove program in Patikang Mangrove Valley, run by PT Chandra Asri Petrochemical Tbk, is a sustainable initiative involving various stakeholders, including companies, governments, academic institutions, media, and local communities. The program aims to integrate education, environmental conservation, and sustainable tourism in mangrove forest preservation, building environmental awareness, increasing stakeholder participation, and empowering local communities in ecotourism management. It emphasizes economic, social, and environmental sustainability, demonstrating a commitment to holistic engagement.This study has several limitations of results due an interpretation, and limited stakeholder engagement. future research can improve the validity, reliability, and relevance of the recommendations.